2008
DOI: 10.1111/j.1365-2621.2007.01633.x
|View full text |Cite
|
Sign up to set email alerts
|

MRI study of bread baking: experimental device and MRI signal analysis

Abstract: An oven dedicated to a magnetic resonance imager (MRI) was designed and constructed for continuous monitoring of the entire baking process. The general aim was to test whether response variables conventionally measured on bread loaves, such as temperature, density, and water loss, were consistent with those reported for similar products baked in classical convection ovens. MRI images acquired during baking are presented and discussed, emphasising the need to develop quantitative MRI methods allowing conversion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 18 publications
0
20
0
2
Order By: Relevance
“…Experimental protocols and methods of measurements have already been detailed in earlier papers (Lucas et al, 2007;Wagner et al, 2008aWagner et al, ,b, 2006 and summarized below.…”
Section: Methodsmentioning
confidence: 98%
“…Experimental protocols and methods of measurements have already been detailed in earlier papers (Lucas et al, 2007;Wagner et al, 2008aWagner et al, ,b, 2006 and summarized below.…”
Section: Methodsmentioning
confidence: 98%
“…It would be interesting to know how far the conclusions drawn at the proving stage (at a moderate temperature) about the collapse and growth of bubbles, especially of larger bubbles, can be applied to the baking stage. Wagner et al demonstrated the feasibility of bread baking inside the magnet of an MRI imager (Wagner et al, 2008;Wagner, Quellec, Trystram, & Lucas, 2007) and this will be the next stage of this work.…”
Section: Shorter Durations Of Pre-fermentationmentioning
confidence: 97%
“…Subsequently, loaves were removed from the pans and allowed to cool for 2 h. MRI baking experiment was performed in a specific oven compatible with MRI. Wagner et al (2008b) showed that the characteristics (specific volumes, water loss, time course changes in temperature, crust coloration) of bread loaves baked in such MRI compatible oven were within the range of values reported in the literature for convection oven.…”
Section: Methodsmentioning
confidence: 49%
“…Bread loaves were baked in a convection oven installed within the probe of the MRI imager (see (Wagner et al 2008b) for a detailed description of this oven). A 1.5T MRI scanner (Magnetom, Avanto, Siemens, Germany) equipped with a head receiver coil was used for measurements.…”
Section: Mri and Temperature Measurementsmentioning
confidence: 99%